An overview of video encryption techniques - Abomhara, Mohamed; Zakaria, Omar; Khalifa, Othman Omran (International Association of Computer Science and Information Technology Press (IACSIT), 2010)
With the rapid development of various multimedia technologies, more and more multimedia data are generated and transmitted in the medical, commercial, and military fields, which may include some sensitive information which should not be accessed by or can only be partially exposed to the general users. Therefore, security and privacy has become an important. Over the last few years several encryption algorithms have applied to secure video transmission. While a large number of multimedia encryption schemes have been proposed in the literature and some have been used in real products, cryptanalytic work has shown the existence of security problems and other weaknesses in most of the proposed multimedia encryption schemes. In this paper, a description and comparison between encryption methods and representative video algorithms were presented. With respect not only to their encryption speed but also their security level and stream size. A trade-off between quality of video streaming and choice of encryption algorithm were shown. Achieving an efficiency, flexibility and security is a challenge of researchers.